Enhancement of the immediate release of paracetamol from alginate beads - Hamed, Samah; Ayob, Farah Amalina; Alfatama, Mulham; Doolaanea, Abd Almonem (Innovare Academic Sciences Pvt Ltd, 2017)
Objective: Alginate beads are not soluble in the acid leading to small portion released in the stomach. This may not be favourable for drugs administered for fast action like paracetamol. So, this study was aimed to increase the immediate release of paracetamol from alginate beads, i.e. the release in the acidic pH. Methods: The beads were prepared by dropwise paracetamol/alginate suspension in divalent cation solution. Two attempts were used to increase the dissolution of paracetamol in the acidic pH. First attempt was by only changing preparation variables: needle size, alginate viscosity and drug loading using 23 full factorial design. The second approach was by adding excipients like carbopol, tween and polyethylene glycol. The beads were characterized for their size, encapsulation efficiency and release profile. Results: First approach, changing preparation variables without excipient adding, helped to increase the drug release in the acid but to a maximum of 26% using a smaller needle, lower drug loading and higher alginate viscosity. However, optimising the formulation with suitable excipients increased the drug release in the acid to 77.3%. The optimised formulation included carbopol 940 (pH sensitive polymer) and tween 80 (facilitates water entry) in the beads, with using barium chloride instead of calcium chloride together with PEG 400 in the complexing solution. Conclusion: To achieve immediate release of paracetamol from alginate beads in the acidic pH, excipients need to be added. Rational selection of excipients is critical to achieve the desired drug release.